Barriers and facilitators to a novel low-barrier hydromorphone distribution program in Vancouver, Canada: a qualitative study. (1st November 2020) - Ivsins, Andrew; Boyd, Jade; Mayer, Samara; Collins, Alexandra; Sutherland, Christy; Kerr, Thomas; McNeil, Ryan
Highlights: Examines engagement with a hydromorphone distribution program in Vancouver, Canada. Barriers included operating hours, dosing schedule, and generic formulations. Facilitators included reliable source of opioids, agency, and program flexibility. Location in overdose prevention site a barrier and facilitator depending on needs. Such programs represent promising intervention to address the overdose crisis. Abstract: Background: North America is experiencing an overdose crisis driven by illicitly-manufactured fentanyl, related analogues, and fentanyl-adulterated drugs. The concept of 'safe supply' has been suggested as a potential measure to address the overdose crisis by providing a regulated alternative to illicit opioids to people at high risk of fatal overdose. In January 2019, a novel hydromorphone tablet distribution program was implemented within an overdose prevention site in Vancouver, Canada's Downtown Eastside neighbourhood. This study explored barriers and facilitators to engagement with this program. Methods: In-depth interviews were conducted with 42 participants enrolled in the hydromorphone tablet distribution program, and over 100 h of ethnographic observation were conducted in and around the study site. Thematic analysis of the interviews and ethnographic observation focused on program operation, including barriers and facilitators to program uptake, access, and engagement. Results: Barriers to program engagement identified include: limited operating hours and dose schedule, co-location within the overdose prevention site (e.g., wait times), and receiving the generic formulation of hydromorphone. Facilitators identified include: having access to a reliable source of opioids, co-location within the overdose prevention site (e.g., low-barrier design), experiences of agency, and program flexibility. Conclusion: Our findings demonstrate key implementation and operational considerations of safe supply programs. In particular, lower-barrier design and operational features should be considered to improve uptake and engagement. Safe opioid supply programs are a promising intervention to address North America's ongoing overdose crisis by providing people at high risk of fatal overdose an alternative to the toxic drug supply.